Error Reduction and Prevention in Surgical Pathology (Springer New York, 2015)
This text focuses on errors in the tissue diagnosis of surgical pathology, how they happen, the best systems to detect these errors, and the best systems to prevent them. As with any form of testing, the test cycle in surgical pathology can be divided into pre-analytic (collection and handling of specimens), analytic (the actual determination of disease or other diagnostic information) and post-analytic (generation of reports and distribution). Error can occur anywhere in the process and all of these steps must be performed optimally so that the correct diagnosis is made and delivered. Error Reduction and Prevention in Surgical Pathology serves as an essential guide to a successfully managed laboratory and contains all relevant information needed to manage specimens and deliver the best diagnosis